KEPENTINGAN PEMERINTAH QATAR DALAM MENGAKUISISI KLUB SEPAK BOLA PARIS SAINT GERMAIN (PSG) MELALUI QATAR SPORT INVESTMENT (QSI) - Fajarindo, Abil; Saeri, Mhd. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research will discuss the interests of the Qatari government in acquiring the Paris Saint Germain (PSG) soccer club through Qatar Sport Investment (QSI) and the various precise steps used by the Qatari government to develop PSG into an outstanding soccer club and one of the best in Europe. Qatar, which is a rich country due to the abundance of their oil and gas natural resources, is now starting to develop their economy in several other fields, one of which is sports, in this case soccer. Qatar is increasingly active in the field of soccer by acquiring a French soccer club, Paris Saint Germain (PSG) and arranging long-term projects with the club. The Qatari government also has several interests to be realized through their ownership of PSG. The research method used in this research is a Qualitative Method supported by data collection methods in the form of library research obtained from various official websites of related parties, credible internet portal websites, as well as various online journals and books related to the topic of discussion. This research is supported by Soft Power Theory and the concept of National Interest. The results of this study found that the main interest of the Qatari government in acquiring the Paris Saint Germain (PSG) soccer club through Qatar Sport Investment (QSI) is economic diversification. Then this is also followed by several interests in other sectors such as International Politics, Economy-Tourism, and Sports. Keywords : Soft Power, Football, Qatar